THE INFLUENCE OF MOTIVATION, WORK ENVIRONMENT, AND TRAINING ON EMPLOYEE PERFORMANCE AT TUALANG REGIONAL GENERAL HOSPITAL (A CASE STUDY OF NON-PERMANENT STAFF AT TUALANG REGIONAL GENERAL HOSPITAL) - Julius Orlando Simanjuntak; Rosa Amanda Saragih; Enia Tami br. Perangin-angin; Cut Fitri Rostina; Fauzi Fauzi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
Tualang Regional General Hospital (RSUD Tualang) is a government healthcare institution dedicated to providing primary, referral, and medical support services while consistently prioritizing social responsibility. As a public service facility, the hospital continuously endeavors to optimize its managerial roles, functions, and governance. Driven by the need to improve employee performance, this study aims to analyze the extent to which Motivation, Work Environment, and Training influence employee performance at Tualang Regional General Hospital. The entire population of 102 individuals was selected as the study sample using non-probability sampling via the saturation sampling method, ensuring that all contract employees were included as respondents. This study employs a quantitative approach, with data collection conducted through observation, interviews, distributed questionnaires, and a review of literature sourced from books and scientific journals. The research findings reveal that motivation and work environment, when considered individually, do not show a positive or significant influence on employee performance. On the other hand, training has a significant and positive influence on employee performance at Tualang Regional General Hospital. Meanwhile, the result of the determination coefficient test of 0.081 indicates that these three variables can only explain 8.1% of employee performance, while the majority of the variance is influenced by other factors outside the scope of this study. Keywords: Motivation, Work Environment, Training, Employee Performance